2013
DOI: 10.1371/journal.pone.0065008
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Heterogeneity in Ecologically Important Climate Variables at Coarse and Fine Scales in a High-Snow Mountain Landscape

Abstract: Climate plays an important role in determining the geographic ranges of species. With rapid climate change expected in the coming decades, ecologists have predicted that species ranges will shift large distances in elevation and latitude. However, most range shift assessments are based on coarse-scale climate models that ignore fine-scale heterogeneity and could fail to capture important range shift dynamics. Moreover, if climate varies dramatically over short distances, some populations of certain species may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(83 citation statements)
references
References 49 publications
2
76
1
Order By: Relevance
“…Both plot‐ and landscape‐scale characteristics had important effects on microclimate variability within forest fragments embedded within human‐modified landscapes (Bonan ). Given the simple topography of our study area, it was surprising that relative elevation had the largest effect size ranging from 0.5 and 2°C, and was comparable to the effect sizes of other studies in mountainous terrains (Ashcroft and Gollan , Ford et al ). Compared to more mountainous areas the velocity of climate change is expected to occur faster in low‐lying regions (Loarie et al ), yet within our study region we found that even subtle variations in microtopography promoted warmer minimum temperatures in forest patches of higher elevation.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Both plot‐ and landscape‐scale characteristics had important effects on microclimate variability within forest fragments embedded within human‐modified landscapes (Bonan ). Given the simple topography of our study area, it was surprising that relative elevation had the largest effect size ranging from 0.5 and 2°C, and was comparable to the effect sizes of other studies in mountainous terrains (Ashcroft and Gollan , Ford et al ). Compared to more mountainous areas the velocity of climate change is expected to occur faster in low‐lying regions (Loarie et al ), yet within our study region we found that even subtle variations in microtopography promoted warmer minimum temperatures in forest patches of higher elevation.…”
Section: Discussionsupporting
confidence: 81%
“…We found that environmental characteristics at both the plot‐ and landscape‐scale were strong drivers of winter microclimates in remnant forest patches. Most studies of microclimates emphasize the role of vegetation and topography (Ashcroft and Gollan , Ford et al ), and although we found strong support for these relationships (e.g. basal area, relative elevation), we also found that characteristics of the surrounding landscape had strong influences on microclimates.…”
Section: Discussioncontrasting
confidence: 55%
“…Fuel reduction could have unintended consequences, since trees moderate climate. Trees filter solar radiation, providing a buffer between CAPs and the atmosphere; removing trees can increase maximum surface temperatures 10 to 40˝C [26]. Oddly, fire suppression which increases tree density may have also made CAPs climates cooler.…”
Section: Implications For Managementmentioning
confidence: 99%
“…Refugia populations are at a greater risk from changing fire patterns [21] due to their predisposition to local extinction because of their small, isolated nature, especially if the plants are fire avoiders [24]. Fire could alter species occurrence directly by killing vegetation or indirectly by altering vegetation's moderating effect on climate [25,26] and the selection pressures on vegetation [27]. In more extreme cases fire can locally extirpate plants if fires are more frequent [28], less frequent [29], or more severe than historical fire regimes [30].…”
Section: Introductionmentioning
confidence: 99%
“…Benefits of fine‐scale heterogeneity have been recognized in terrestrial landscapes as functions of vegetation cover and small‐scale topographical features (Ford et al. ) and in rivers due to dendritic structure and landscape gradients (Brown , Thompson and Townsend ), but lakes have received less attention as systems with spatial heterogeneity on scales relevant to mobile organisms. Failure to recognize and account for this heterogeneity within lakes can mislead our understanding of biological responses to environmental changes (Luoto and Heikkinen ).…”
Section: Introductionmentioning
confidence: 99%